Pengembangan Media Komik Berkarakter untuk Materi Hak dan Kewajiban pada Mata Pelajaran Pendidikan Pancasila Kelas IV SDN Tisnogambar 02 Jember - Dian Lailatul Fitria (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study was motivade by the fact that the use of learning media in Pancasila education is still limited to books, and teaching is still conducted conventionally, with a predominance of lectures. This results in minimal interaction between students, boredom in learning, and difficulty in understanding the material. Learning needs to be supported by interesting media that can increase interest in learning and reduce boredom. This study aims to develop character based comic media and analyze the validity, effectiveness, and practicality of character-based comic media for the rights and obligations material in the Pancasila education subject for fourth grade students at SDN Tisnogambar 02 Jember. This study uses a development research design based on the Borg and Gall model through eight stages. The developed media was evaluated based on validity, effectiveness, and practicality. The validation results showed a score of 96,07, categorized as highly acceptable. The effectiveness test yielded a t-value of 8,241, which is greater than the critical t-value of 2,005, indicating a significant improvement in students learning outcomes. The relative effectiveness test yielded a result of 68%, falling into the high effectiveness category. The practicality test, conducted through a student response questionnaire, scored 95, categorized as highly effective. Based on the tests conducted, it was concluded that the character based comic media is valid, effective, and practical for use in learning
Reaploud Repository February 2026_Hasyim
Keywords: Character Comic Media; Pancasila Education; Rights & Obligations Material